High electricity generation and COD removal from cattle wastewater in microbial fuel cells with 3D air cathode employed non-precious Cu2O/reduced graphene oxide as cathode catalyst. (1st April 2020) - Xin, Shuaishuai; Shen, Jianguo; Liu, Guocheng; Chen, Qinghua; Xiao, Zhou; Zhang, Guodong; Xin, Yanjun
Abstract: In this study, we synthesized a non-precious Cu2 O decorated reduced graphene oxide composite (Cu2 O/rGO) by a facile and direct reduction strategy and evaluated the electricity generation and COD removal performance of MFCs with Cu2 O/rGO as cathode catalyst in treating cattle wastewater. The Cu2 O/rGO with the mass Cu(Ac)2 /GO ratio of 450:50 exhibited the highest catalytic activity by cyclic voltammetry (CV) experiment. The large surface area (363.9 m 2  g −1 ) of Cu2 O/rGO with numerous mesoporous exhibited higher exchange current density (12.38 μA cm −2 ) and lower War-burg impedance (21.82 Ω) comparing with Pt/C (11.99 μA cm −2, 102.10 Ω), and contributed to 4-electron ORR. Notably, the maximum output voltage, power density and coulombic efficiency of MFC with 3D air cathode employed Cu2 O/rGO catalyst reached 0.165 V, 1362 mW m −2 and 54.9%, respectively, which were higher than those (0.152 V, 1166 mW m −2 and 53.5%) with 3D air cathode employed Pt/C catalyst in treating cattle wastewater. Moreover, the average COD removal rate of MFC with Cu2 O/rGO catalyst reached 71.5%, which were higher than those 69.8% with Pt/C catalyst. Generally, the MFC with 3D air cathode employed non-precious Cu2 O/rGO catalyst instead of Pt/C catalysts is a promising method for simultaneous electricity generation and cattle wastewater treatment. Highlights: Cu2 O nanoparticles/rGO cathode catalyst was synthesized for ORR in MFC. Cu2 O/rGO with mass Cu(Ac)2 /GO ratio of 450:50 had the highest catalytic activity. Structural characterization and electrocatalytic property of Cu2 O/rGO were explored. Electricity generation and COD removal from cattle wastewater in MFCs were evaluated.